2022
DOI: 10.1108/et-05-2021-0164
|View full text |Cite
|
Sign up to set email alerts
|

Blended learning in entrepreneurship education: a systematic literature review

Abstract: PurposeCurrent research lacks a clear definition of blended learning in entrepreneurship education (EE), a comprehensive overview of the recent research, and a conceptualization of different types of blends with their respective challenges and advantages. In response to that, the author systematically reviewed the literature on blended learning in EE and developed four archetypes of blends for entrepreneurship educators.Design/methodology/approachThe author conducted a systematic literature review and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…Термiн (слова, що вживаються для його визначення) українська, змiшане навчання [10,46,86,87,89,124], комбiноване навчання [115,119,126] рiзновид гiбридної методики, коли вiдбувається поєднання онлайн навчання, традицiйного та самостiйного навчання. Мається на увазi не просто використання сучасних iнтерактивних технологiй на додаток до традицiйних, а якiсно новий пiдхiд до навчання, що трансформує, а iнодi i "перевертає" клас змiшане навчання албанська, mësimi i përzier [26,49] është një qasje ndaj arsimit dhe edukimit që kombinon materiale arsimore në internet dhe mundësi tjera për ndërveprim në internet me metodat tradicionale të mësimdhënies klasore në shkollë змiшане навчання ("комбiнування") англiйська, blended learning [27, 45,70,71] the combination of online educational materials and interactions with traditional classroom teaching blended learning ("комбiнування") болгарська, хибридно обучение [23,130] хибридно или смесено обучение е подход в ученето и съответно в педагогиката в образованието, който съчетава онлайн образователни материали и възможности за взаимодействие онлайн с традиционни методи на класната стая или студентска зала, като лекционна среда гiбридне, змiшане навчання данська, blended learning [14,47,129] er et begreb der anvendes inden for uddannelsesverdenen. Det betegner typisk kombinationen af e-learning og tilstedevaerelseskurser, f.eks.…”
Section: мова термIн визначенняunclassified
“…Термiн (слова, що вживаються для його визначення) українська, змiшане навчання [10,46,86,87,89,124], комбiноване навчання [115,119,126] рiзновид гiбридної методики, коли вiдбувається поєднання онлайн навчання, традицiйного та самостiйного навчання. Мається на увазi не просто використання сучасних iнтерактивних технологiй на додаток до традицiйних, а якiсно новий пiдхiд до навчання, що трансформує, а iнодi i "перевертає" клас змiшане навчання албанська, mësimi i përzier [26,49] është një qasje ndaj arsimit dhe edukimit që kombinon materiale arsimore në internet dhe mundësi tjera për ndërveprim në internet me metodat tradicionale të mësimdhënies klasore në shkollë змiшане навчання ("комбiнування") англiйська, blended learning [27, 45,70,71] the combination of online educational materials and interactions with traditional classroom teaching blended learning ("комбiнування") болгарська, хибридно обучение [23,130] хибридно или смесено обучение е подход в ученето и съответно в педагогиката в образованието, който съчетава онлайн образователни материали и възможности за взаимодействие онлайн с традиционни методи на класната стая или студентска зала, като лекционна среда гiбридне, змiшане навчання данська, blended learning [14,47,129] er et begreb der anvendes inden for uddannelsesverdenen. Det betegner typisk kombinationen af e-learning og tilstedevaerelseskurser, f.eks.…”
Section: мова термIн визначенняunclassified
“…Blended learning can integrate multiple components, e.g., learning situations where online, physical and working situations can be included; knowledge acquisition mechanisms, e.g., retention and attrition; affective elements in learning, e.g., motivation, satisfaction, encouragement, and cognitive loads; and participants, e.g., teachers, learners, and designers. It could be a complicated blend including the traditional, the for-and in-actions, and experiential factors (Viebig, 2022).…”
Section: Introduction Definitions Of Blended Learningmentioning
confidence: 99%
“…While gamification was initially used within the teaching of computer science-based curricula (Dicheva et al, 2015), this study considers the effectiveness of using game-based methods within the entrepreneurial classroom. It has been suggested that there is both a science and art involved in the teaching of entrepreneurship (Henry et al, 2005;Pittaway and Cope, 2007;Neck and Greene, 2011;Lack eus and Middleton, 2015;Ramsgaard and Christensen, 2016;Lyons and Buckley, 2021;Takemoto and Oe, 2021;Viebig, 2022;Nikitina et al, 2022). The "science" relates to business skills and knowledge, which are feasible to teach using conventional methods.…”
Section: Literature Reviewmentioning
confidence: 99%